2017
DOI: 10.15625/2525-2518/55/3/8820
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Elemental and Organic Carbon in Atmospheric Nanoparticles at Different Sampling Locations in Vietnam

Abstract: Atmospheric ultrafine particles (NPs or PM0.1) were investigated at a roadside of Nguyen Van Cu road (Vinacomin) and at a mixed site in the Hanoi University of Science and Technology (HUST) in Hanoi, Vietnam. The sampling was conducted during a rainy reason and a dry season to determine the characteristics of atmospheric elemental and organic carbon in the nanoparticles. The relative contributions of organic carbon (OC) and elemental carbon (EC) to total carbon (TC) at HUST were 83.7 – 85.0% and 15.0–16.3 %, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The concentration of nanoparticles at QO_RS burning site was 11.5 ± 3.9 μg/m 3 . Despite its low mass concentration, nanoparticles have been recognized to be more important and harmful than the larger size particles such as PM 2.5 at the same mass concentration [20,21]. Considering the mass concentration of fine particles, the mass concentration of PM 2.5 was 79.7 ± 46.5 μg/m 3 and 90.8 ± 33.2 μg/m 3 at DA_RS burning site and QO_RS burning site, respectively.…”
Section: Mass Concentration Of Particles In Rs Burning Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of nanoparticles at QO_RS burning site was 11.5 ± 3.9 μg/m 3 . Despite its low mass concentration, nanoparticles have been recognized to be more important and harmful than the larger size particles such as PM 2.5 at the same mass concentration [20,21]. Considering the mass concentration of fine particles, the mass concentration of PM 2.5 was 79.7 ± 46.5 μg/m 3 and 90.8 ± 33.2 μg/m 3 at DA_RS burning site and QO_RS burning site, respectively.…”
Section: Mass Concentration Of Particles In Rs Burning Periodmentioning
confidence: 99%
“…Numerous studies on size distribution and mass concentration of particles in the atmosphere have been conducted [12 -18]. In Viet Nam, several studies focused on mass concentration of nanoparticles and fine particles, carbonaceous components of nanoparticles at urban locations in Ha Noi [19,20]. Tran et al [21] assess the air quality in school environment in Ha Noi focus on the mass-size distribution and found that ultrafine particles accounted for around 15 -20 % wt/wt while fine particles (PM 2.5 ) made up almost 80 % wt/wt of PM 10 .…”
Section: Introductionmentioning
confidence: 99%